Assessment of the causes and extent of damage to trees of Olea europaea subsp. cuspidata (Wall. and G.Don) Cif. (wild olive) in the mountains of Oman - Thuraiya Al Jabri; Alastair Culham; Richard H. Ellis (PLoS ONE, 2026)
Olea europaea subsp. cuspidata (Wall. and G.Don) Cif. (wild olive) is one of the key woody species in the mountain habitats of Oman. Wild olive trees are scattered, isolated, and at risk from several threats including climate change, urbanization, browsing, human activity, and the introduction of non-native species. One hundred and eighty-four trees from eight locations in three mountain ranges (Eastern Hajar, Western Hajar, and Dhofar) in Oman were assessed. The extent of damage to trees caused by browsing, drought (dead branches), and human activity (cutting and burning) was scored between 10 June and 5 July 2020. Most olive trees in these mountain ranges exhibited moderate damage, ranging from 21% to 45%, while 29% of wild olive trees experienced high levels of damage, ranging from 45% to 64%. Wild olive trees in the Western Hajar Mountains and Dhofar Mountains showed the greatest damage. Tree height differed significantly among these eight locations across Oman. There was a negative correlation between tree damage and tree height and a positive correlation between tree damage and site slope but no correlation between tree damage and site altitude. No natural regeneration of wild olive was detected in any of the eight locations. Urbanization and over-browsing are putting wild olive at high risk. Action to protect these mountain habitats will be essential to conserve this ecologically important subspecies in these mountains.